Reverse modelling of natural rock joints using 3D scanning and 3D printing. (March 2016) - Jiang, Quan; Feng, Xiating; Gong, Yanhua; Song, Leibo; Ran, Shuguang; Cui, Jie
Abstract: In order to overcome the deficiency of natural joint specimens with the same surface morphology for experimental studies, we present a technical method for replicating natural joint specimens that incorporates two advanced techniques – three-dimensional (3D) scanning and 3D printing – using computer-aided design (CAD) as the 'bridge'. This method uses an optical scanning apparatus and CAD techniques to reconstruct a virtual joint specimen with the natural rock's joint morphology, and a 3D printer then manufactures a physical mould based on the virtual joint specimen for casting concrete or plastic specimens quickly and accurately. Quality verification clearly indicated that this method reduces the experimental errors originating from the discrepancies between replicating specimens containing natural joint's morphology.